New found hope for antibiotic discovery: lipid II inhibitors - Ng, Vivian; Chan, Weng C. (Wiley, 2016)
Research into antibacterial agents has recently gathered pace in light of the disturbing crisis of antimicrobial resistance. The development of modern tools offers the opportunity of reviving the fallen era of antibacterial discovery through uncovering novel lead compounds that target vital bacterial cell components, such as lipid II. This paper provides a summary of the role of lipid II as well as an overview and insight into the structural features of macrocyclic peptides that inhibit this bacterial cell wall component. The recent discovery of teixobactin, a new class of lipid II inhibitor has generated substantial research interests. As such, the significant progress that has been achieved towards its development as a promising antibacterial agent is discussed.